Contrastive Analysis of Onomatopoeias and Onomatopoeic Derivatives in the Turkish and Bosnian Languages - Bakšić, Sabina (Prilozi za orijentalnu filologiju, 2017)
This paper contrasts onomatopoeias and onomatopoeic derivatives in the Bosnia and Turkish languages. The sound symbolism with its subclasses: bodily, imitative, and synaesthetic sound symbolism, and with its forms: reduplication, the use of unusual segments and the copula of a particular phoneme class in a word with its semantic field, served as a framework for the analysis. In the imitative part of the sound symbolism, certain resemblances were noticed between these two languages, which makes us think that there is a certain link between the way of a particular sound articulation and the meaning of the word in which it occurs. The real differences manifested just in synaesthesia, where the majority of the Turkish onomatopoeias and onomatopoeic derivatives can be translated only descriptively. Any consideration of onomatopoeias implies the question about the nature of the language symbol. This paper supports a view that the doubt about the motivation and/or non-motivation of the symbol is superfluous as the symbol is at the same time both motivated and arbitrary.